2022
DOI: 10.1186/s12936-022-04253-z
|View full text |Cite
|
Sign up to set email alerts
|

Population knowledge, attitudes and practices towards malaria prevention in the locality of Makenene, Centre-Cameroon

Abstract: Background To contribute to the mission of the National Malaria Control Programme (NMCP) and guide future interventions in Cameroon in general, and in Makenene in particular, this study assessed the knowledge, attitudes and practices of the population of Makenene towards the fight against malaria. Methods Using a semi-structured questionnaire, a descriptive cross-sectional household community survey was carried out in randomly selected households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…Comparable findings have been reported in previous studies [16,18,22]. However, studies in northwest Ethiopia [21], Cameroon [42], and Karachi [41] recorded a higher proportion of respondents with good practices, whereas the proportion in Laos was only 5.7% [43].…”
Section: Discussionsupporting
confidence: 69%
“…Comparable findings have been reported in previous studies [16,18,22]. However, studies in northwest Ethiopia [21], Cameroon [42], and Karachi [41] recorded a higher proportion of respondents with good practices, whereas the proportion in Laos was only 5.7% [43].…”
Section: Discussionsupporting
confidence: 69%
“…Other studies have demonstrated a statistically significant relationship between the level of knowledge and the practices of using and maintaining long-lasting insecticideal nets. [11][12][13] The respondents' attitudes are also significantly related in an inverse manner to the practices of using and maintaining long-lasting insecticidal nets. The majority of respondents agree that following the recommended maintenance guidelines can prolong the lifespan of the insecticidal nets.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan berhubungan dengan kejadian filariasis dan merupakan faktor yang bisa mengurangi risiko kejadian filariasis. 26 Hal yang sama dilaporkan di Kecamatan Kodi Balaghar, Kabupaten Sumba Barat Daya, bahwa pengetahuan memiliki hubungan signifikan dengan kejadian filariasis. 27 Hasil penelitian di Desa Tamansari dan Desa Cimanggis menunjukkan secara umum responden memiliki sikap positif.…”
Section: Pembahasanunclassified
“…Hasil ini sejalan dengan beberapa penelitian yang juga menemukan sebagian besar sikap responden adalah positif tentang filariasis, 18,28 namun berbeda dengan penelitian pada komunitas penduduk yang justru menemukan sikap responden yang kurang tentang filariasis. 26 Komponen sikap responden yang kurang dalam penelitian ini adalah sikap terhadap filariasis yang jika tidak diobati dianggap hanya menimbulkan sakit biasa. Hal ini kemungkinan disebabkan karena persepsi responden yang melihat langsung penderita yang masih tetap dapat beraktivitas mencari nafkah dan bersosialisasi dengan masyarakat lainnya.…”
Section: Pembahasanunclassified